Genetic diversity of Mycobacterium tuberculosis isolates from northwest of Iran during COVID-19 era - Peyvand Kashi; Farzaneh Pakdel; Mohammad Hossein Soroush Barhaghi; Mohammad Ahangarzadeh Rezaee; Sepehr Taghizadeh; Javid Sadeghi; Mehdi Yousefi; Reza Ghotaslou; Mohammad Asgharzadeh; Pourya Gholizadeh; Hossein Samadi Kafil (Egyptian Journal of Medical Human Genetics, 2023)
Abstract Background Tuberculosis (TB) is considered one of the most infectious diseases in the world. In this study, we intended to examine the epidemiology of tuberculosis by MIRU-VNTR to define the changes that occur in the transmission of tuberculosis in the region during the COVID-19 era. A total of 120 Mycobacterium tuberculosis isolates were collected from sputum samples of patients referred to East Azerbaijan Center TB from December 2020 to August 2021. Demographic information such as age, sex, place of birth, previous TB history, and relevant medical data was collected. The proportion method was performed for drug susceptibility testing, and the PCR-based MIRU-VNTR method was applied to identify molecular epidemiology relationships. Results The isolates were collected from 78 male (65%) and 39 female (32.5%) Iranian patients and 3 (2.5%) Azerbaijani patients. Ninety-three distinct patterns were identified including 15 clustered patterns and 36 unique patterns. The largest cluster was composed of seven isolates. Furthermore, one cluster with 5 members, four clusters with 3 members, and nine clusters with 2 members. In MIRU-VNTR typing, 75 clusters belonged to the Tabriz region and just 3 to the Republic of Azerbaijan. All isolates were sensitive to rifampin, isoniazid, and ethambutol. Conclusions Results of the current study showed COVID-19 pandemic had a direct effect on the transmission and diagnosis of tuberculosis. Less diagnosis and less clustering can indicate public controls and hygiene, and the use of masks had a direct effect on the transmission and diagnosis of tuberculosis. However, misidentification and less focus on other respiratory infections are expected during the pandemic. Studies on the co-infection of COVID-19 and tuberculosis and the role of mask and sanitization against TB are strongly recommended.